The Influence of Corporate Governance Structures on Financial Distress: A Study of Coal Mining Companies - Agustina, Yuli; Anwar, Choisi Elgamalia (KnE Social Sciences, 2021)
The purpose of this research was to analyze the effect of corporate governance mechanisms on financial distress, through the measurement of board of directors, board of commissioners, independent ownership structures and managerial ownership structures. The sample consisted of coal mining companies listed on the Indonesian Stock Exchange from 2013 to 2017 and a purposive sampling method was used. Data were analyzed using descriptive analysis and multiple linear regression. The results confirmed that the size of the board of commissioners and institutional ownership had no effect on conditions of financial distress. This was possible because the board of commissioners functions as supervisor in the company, but sometimes it did not carry out its role to its full potential. Meanwhile, institutional ownership was expected to encourage more optimal supervision of management performance so that agency costs could be minimized, but this could not be proven. The size of the board of directors had a significantly positive effect on finances distress. The size of the board of directors could indicate collusion in the company and thus the possibility of experiencing financial distress was greater. Managerial ownership had a significantly negative effect on conditions of financial distress. With an increase in ownership by managers, managers could immediately feel the benefits and losses of the decisions taken. Keywords: board size, the company’s health condition, corporate governance, financial distress, the Altman Z-Score, the number of boards.